Pengelolaan Kesan Tokoh Utama Umaru Doma dalam Anime Himouto! Umaru-chan - Diva Khalia Rafifahtuzzahra; Heri Widodo; Muammar Kadafi (Jurnal Sakura : Sastra, Bahasa, Kebudayaan dan Pranata Jepang, 2025)
This study examines the impression management of the main character, Umaru Doma, in the anime Himouto! Umaru-chan using Erving Goffman’s dramaturgical theory. The research focuses on three aspects behavior, academics, and how Umaru expresses her desires analyzed through two interaction areas: front stage and back stage. In the front stage, Umaru presents herself as an ideal, active, friendly, and accomplished student to meet social expectations, while in the back stage, she reveals a more relaxed and lazy side when at home. This study also explores Japanese cultural concepts such as wa (harmony), ganbaru (perseverance), and amae (emotional dependence) to understand the impression management strategies Umaru employs. The results show that Umaru consciously portrays a specific image in public spaces to gain social acceptance and sympathy, while in private, she freely expresses her true self without social pressure. These findings reflect how individuals may use impression management in daily interactions to achieve personal goals